Global Focus: Asia Pacific Business Schools Librarians' Group - Delaney, Kitty (Michigan Publishing Services, 2022)
The Asia Pacific Business Schools Librarians' Group (APBSLG) was established in 2003 when the INSEAD Asia campus library hosted the inaugural meeting in Singapore. Members come together at an annual conference, usually of two-day duration. The location rotates among members, and it is an opportunity to experience different cultures, sample delicious cuisines, share innovative ideas, discuss challenges, and engage with professional colleagues. Because of the pandemic, the APBSLG held virtual annual conferences in 2020 and 2021.